The Political-Economy of Community Forests in West Sumatra: Contestation of the Nagari Forests Management (1970–2024) - Utami, Septi; Mustafa, Hanif Risa (Analisis Sejarah, 2025)
This study examines the management of community forests, specifically nagari forests, in West Sumatra. This research is vital because studies on nagari forests in West Sumatra tend to be descriptive and technocratic, without highlighting the historical, political, and economic dynamics that shape forestry policy. This study analyzes community adaptation and resistance strategies in conserving customary-based forests. This research uses a historical method, with heuristics, source criticism, interpretation, and historiography. The results show that nagari forest management in West Sumatra significantly impacts the local economy, ecological resilience, and social structure of the nagari. Forests provide economic, social, and environmental benefits to the community. However, the government's position is unclear. On the one hand, the government encourages community forest management. On the other hand, the government facilitates large-scale concessions to private companies.